Analisis Risiko Produksi Dan Pendapatan Usahatani Padi di Desa Hargomulyo Kecamatan Sekampung Kabupaten Lampung Timur: Analisis Risiko Produksi Dan Pendapatan Usahatani Padi di Desa Hargomulyo Kecamatan Sekampung Kabupaten Lampung Timur - Nurwahid, Azis; Mardliyah, Ainul; Syahputra, Fikri; Musti Ariska, Feby (Politeknik Negeri Lampung, 2023)
Effective resource allocation is one way to meet food needs, especially rice. So it is necessary to increase production so that farmers income increases, but in farming there are farming risks such as production risk and income risk. This research aims to 1) analyze rice farming income in Hargomulyo village Sekampung district east Lampung regency; 2) analyze the level of production risk and income risk of rice farming in Hargomulyo village Sekampung district east Lampung regency. The research method uses a survey method with sampling using the simple random sampling technique with a sample size of 28 rich farmers. The above research objectives were analyzed using income analysis (R/C ratio) and coefficient of variation (CV). The research results showed that: 1) rice farming income was Rp. 7.707.271/0,53 Ha with r/c analysis of 2,46 > 1 which means profitable; 2) production risk level with a CV value of 0,48 < 0,5 which means it has a low risk and income risk with a CV value of 0,57 > 0,5 which means it has a high risk due to reduced production due to pest attacks, shortages irrigation water, as well as selling the products to middlemen.